Can the epidemiology of zoonotic disease be studied in routine health records? A feasibility study of the Clinical Practice Research Datalink (CPRD) - Chris D. Poole; James Frost; Georgina Tarrant; Andrew Hancock; Isaac Odeyemi; Niels Wuyts; Alasdair J.C. Cook (One Health, 2025)
Zoonotic diseases pose significant challenges to public health, creating substantial societal and economic burdens. Current surveillance systems rely primarily on laboratory-confirmed cases and statutory notifications, which may underestimate true disease prevalence. This study investigates the feasibility of using routine electronic health records from the Clinical Practice Research Datalink (CPRD) as an alternative or complementary approach to zoonotic disease surveillance in the United Kingdom.The objective was to compare incidence of zoonotic diseases reported by Public Health England (PHE) with new diagnoses observed in the CPRD and to assess the potential of routine healthcare records for epidemiological monitoring.A comprehensive retrospective cohort study was conducted over a ten-year period (2009–2019), examining ten notifiable zoonotic diseases. Data were sourced from the CPRD, including primary care records, Hospital Episode Statistics, and Office for National Statistics death certification. Age-sex-standardised annual incidence was calculated using Poisson regression.The study analysed 10,441 new zoonotic disease cases in CPRD over 152 million person-years, compared to 32,167 cases reported by PHE over 631 million person-years. Overall, there was good correspondence between CPRD and PHE incidence data (R-square: 0.571). Lyme disease emerged as the most common zoonotic disease in CPRD (3.67 incident cases per 100,000 person-years) while pasteurellosis was underreported.The CPRD demonstrates potential as a complementary surveillance tool for zoonotic diseases. The study reveals both strengths and limitations of routine healthcare records in epidemiological monitoring, highlighting the need for integrated, multi-source approaches to disease surveillance including data-linkage with animal health records.This research provides critical insights for developing more comprehensive zoonotic disease monitoring strategies.